PEDAGOGIA ITALIANĂ ÎN CONTEXTUL ŞTIINŢELOR EDUCAŢIEI - USM ADMIN (Moldova State University, 2011)
Pedagogy has known in the second half of the 20 th century a radical change, with the apparition and multiplication of the educational sciences, which has determined the redefining of identity, the renewal of limits and the moving of the epistemological centre of weight of pedagogy. The switch from singular to plural, from pedagogy to the sciences of education, has been a crucial moment in the evolution of pedagogy. In our opinion, pedagogy holds a central part in respect to the other sciences of education, as no science of education appears unless it has a pedagogic basis. General pedagogy furnishes the general reference framework, ensures the epistemological basis of all sciences that are preoccupied with the study of education.